2014
DOI: 10.3390/rs61110835
|View full text |Cite
|
Sign up to set email alerts
|

MODIS Inundation Estimate Assimilation into Soil Moisture Accounting Hydrologic Model: A Case Study in Southeast Asia

Abstract: Flash Flood Guidance consists of indices that estimate the amount of rain of a certain duration that is needed over a given small basin in order to cause minor flooding. Backwater catchment inundation from swollen rivers or regional groundwater inputs are not significant over the spatial and temporal scales for the majority of upland flash flood prone basins, as such, these effects are not considered. However, some lowland areas and flat terrain near large rivers experience standing water long after local prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Data assimilation is a method that combines a model with observation data [ 20 , 42 , 43 ]. In this paper, the WOFOST model under potential production levels (suitable water and nutrients), was assimilated with the observation data.…”
Section: Methodsmentioning
confidence: 99%
“…Data assimilation is a method that combines a model with observation data [ 20 , 42 , 43 ]. In this paper, the WOFOST model under potential production levels (suitable water and nutrients), was assimilated with the observation data.…”
Section: Methodsmentioning
confidence: 99%
“…Legal and illegal deforestation activities are significantly disturbing the rainfall-runoff processes, with disastrous effects on a considerable number of Romanian rural communities. Choi (2013) and Posner et al (2014), showed the importance of mapping products and simulation models for the small watershed protection and flood prevention for refined prognosis of water system evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the R2O process is similar for other components of the FFGS. An example is the effective landsurface component parametrization and validation using a variety of evolving remotely sensed data and products (e.g., Posner et al 2014;Shamir and Georgakakos, 2014). Another example is the multi-model ensemble forecasting and uncertainty characterization; from the theory in Ntelekos et al 2006 and, to application in the operational systems by including forecasts from several mesoscale atmospheric models, and to the current effort to use several land-surface component models as well.…”
Section: Design Of the Ffgsmentioning
confidence: 99%